2004
DOI: 10.1016/j.cardiores.2004.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular coupling through gap junctions masks M cells in the human heart

Abstract: The manifestation of M cells is absent in the human heart, probably by effective intercellular coupling, turning them functionally "invisible".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 34 publications
1
49
0
Order By: Relevance
“…For instance, measurement of the human ventricles during cardiac surgery, rather than isolated cells or a ventricular wedge, produced no significant transmural heterogeneity of repolarization (42). The electronic cancellation effect introduced by intercellular coupling through gap junctions is considered the cause of these observations in intact preparations (5,41), although experimental artifact has also been suggested (1). During surgery or in animal experiments, subjects receive anesthetic agents that may block sodium and/or delayed rectifier potassium currents, causing preferential shortening of the APD of M cells (31).…”
mentioning
confidence: 99%
“…For instance, measurement of the human ventricles during cardiac surgery, rather than isolated cells or a ventricular wedge, produced no significant transmural heterogeneity of repolarization (42). The electronic cancellation effect introduced by intercellular coupling through gap junctions is considered the cause of these observations in intact preparations (5,41), although experimental artifact has also been suggested (1). During surgery or in animal experiments, subjects receive anesthetic agents that may block sodium and/or delayed rectifier potassium currents, causing preferential shortening of the APD of M cells (31).…”
mentioning
confidence: 99%
“…3, panel IV, as well as in previous studies (Yan et al, 1998b;Gima and Rudy, 2002;Idriss and Wolf, 2004;Ritsema van Eck et al, 2005). It should be noted however, that, while there is a large body of evidence supporting the existence of transmural heterogeneities in ionic currents and electrophysiological properties of ventricular tissue, some experimental studies have documented little or no transmural differences in APD in vivo (Anyukhovsky et al, 1996(Anyukhovsky et al, ,1999Taggart et al, 2001;Conrath et al;.…”
Section: Transmural Electrophysiological Heterogeneities In the Ventrmentioning
confidence: 54%
“…Numerous studies have demonstrated that the coupling of cardiac gap junction is related closely to transmural dispersion of repolarization (TDR), 6,[8][9][10] and the uncoupling of gap junction will lead to an amplification of TDR, which is considered as a substrate for cardiac arrhythmogenesis. The present study investigated the underlying mechanisms for PMA-induced arrhythmias and the antiarrhythmic effect of AAP10 on PMA- .…”
Section: Discussionmentioning
confidence: 99%